1997
DOI: 10.1093/ajcn/65.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced generation of interleukins 1 beta and 6 may contribute to the cachexia of chronic disease

Abstract: The cachexia of disease may be promoted by proinflammatory cytokines, eg, interleukin (IL) 1 beta, tumor necrosis factor alpha (TNF-alpha), and IL-6. These, as well as some antiinflammatory cytokines, eg, IL-1 receptor antagonist (IL-1ra), IL-10, and transforming growth factor beta 1 (TGF-beta 1), were analyzed in serum (IL-6, IL-1ra, IL-10, TGF-beta 1) and stimulated blood monocytes (IL-1 beta, TNF alpha, IL-6) obtained from elderly patients with protein-energy malnutrition (PEM). Twenty-one uninfected malnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 37 publications
6
44
0
5
Order By: Relevance
“…The sensitivity to low doses of LPS was increased in malnourished children relative to healthy controls. While these findings are consistent with several lines of evidence from the literature (11)(12)(13)(14)(15), they are clearly at variance with those reported by other investigators addressing the same issue in other countries (7,9). It is not clear, at present, whether these discrepancies can be reconciled without further studies, but methodological differences may play a major role.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The sensitivity to low doses of LPS was increased in malnourished children relative to healthy controls. While these findings are consistent with several lines of evidence from the literature (11)(12)(13)(14)(15), they are clearly at variance with those reported by other investigators addressing the same issue in other countries (7,9). It is not clear, at present, whether these discrepancies can be reconciled without further studies, but methodological differences may play a major role.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies describe a marked deficit in TNF-α, IL-1, and IL-6 production in severe childhood malnutrition (7)(8)(9)(10) while others have reported that starvation increases TNF-α production (11). Furthermore, production of IL-1 and IL-6 is increased in malnourished subjects free from infection (12), and production of TNF-α and IL-1 proceeds normally in animal models of protein malnutrition (13,14). Finally, increased levels of soluble TNF-α receptors, which are induced by sustained increases in TNF-α receptors as part of regulatory mechanisms (15)(16)(17)(18), have been detected in malnourished children (19), suggesting that these children are capable of significant TNF-α production.…”
Section: Introductionmentioning
confidence: 99%
“…Injuryinduced release of stress hormones and proinflammatory cytokines such as tumour necrosis factor-α, IL-1β and IL-6 may sustain a prolonged catabolic state characterized by nitrogen loss (Weissman 1990, Cederholm et al 1997) and insulin resistance, the latter often presenting as hyperglycemia despite elevated levels of insulin, exacerbating the depletion of muscle protein and lean body mass. Although insulin resistance may be physiological in some situations, it is generally not beneficial for recovery (Thorell et al 1999, van den Berghe et al 2001.…”
Section: Peroperative Catabolic Stressmentioning
confidence: 99%
“…In RA as in other chronic diseases, the systemic activity of inflammatory mediators, for example, cytokines as interleukin (IL)-1beta, tumour necrosis factor (TNF) and IL-6 have been indicated as inducers of muscle wasting (Roubenoff et al, 1992;Cederholm et al, 1997). Also the resulting disability has impact on the nutritional status in these patients (Hernandez-Beriain et al, 1996).…”
Section: Introductionmentioning
confidence: 99%